2018
DOI: 10.3233/bmr-170806
|View full text |Cite
|
Sign up to set email alerts
|

Clinical predictors of the medical interventions provided to patients with low back pain in the emergency department

Abstract: Most patients present to the ED with acute exacerbations of chronic low back pain. Risk factors for a serious condition are common, but rarely do they develop. Racial disparities and psychosocial factors had concerning relationships with clinical decision-making.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
20
2
2

Year Published

2018
2018
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 24 publications
(29 citation statements)
references
References 14 publications
0
20
2
2
Order By: Relevance
“…The prevalence of a cauda equina syndrome or radiculopathy with weakness was 1.9% in one prospective observational study. 5 In retrospective studies, a cauda equina syndrome was found in 0.3-0.5%, 26,27 and in patients with neurological deficits in 1.7%. 24 One retrospective study reported a higher prevalence of spinal cord/cauda equina compression (15.5%) in patients referred to an orthopedic team because of neurological symptoms.…”
Section: Prevalence Of Specific Spinal Pathologiesmentioning
confidence: 95%
See 1 more Smart Citation
“…The prevalence of a cauda equina syndrome or radiculopathy with weakness was 1.9% in one prospective observational study. 5 In retrospective studies, a cauda equina syndrome was found in 0.3-0.5%, 26,27 and in patients with neurological deficits in 1.7%. 24 One retrospective study reported a higher prevalence of spinal cord/cauda equina compression (15.5%) in patients referred to an orthopedic team because of neurological symptoms.…”
Section: Prevalence Of Specific Spinal Pathologiesmentioning
confidence: 95%
“…4 The prevalence in the ED setting is unclear and it is reasonable to assume it to be higher compared to the primary care setting. 5 Red flags are signs/symptoms that help to identify patients at risk for a serious underlying disease. 6 However, there is no consensus on which red flags should be screened for: 16 guidelines recommended 46 different red flags.…”
Section: Introductionmentioning
confidence: 99%
“…Previous research demonstrated a relationship between dynamic physical tests, self-reported LBP and reduced function. 38 However, such research has been neglected in recent decades 29–32 as focus shifted towards physiological and radiological findings 9 10 and biopsychosocial attributes. 3 6 7 11 Grönblad et al 38 showed three physical exercises (repetitive sit-ups, squats and EIL) had a positive correlation with LBP.…”
Section: Discussionmentioning
confidence: 99%
“…These include: medical investigative relationships such as radiological 23 24 or physiological findings 25–27 that have produced mixed results even from the same study 28 and biopsychosocial considerations 29–32 or a mixture of these. 9–11 In contrast, modifiable factors 33 34 including movement patterns, 14 35 physiological loads 36 and exercise capacity 37 38 receive limited attention yet they significantly influence LBP morbidity and symptomology, 1 2 being recognised as potentially able to prevent LBP. 11 20 …”
Section: Introductionmentioning
confidence: 99%
“…Low‐back pain (LBP) is a frequent presentation to the emergency department (ED) . While some ED studies indicate that serious medical conditions among patients presenting to the ED with LBP are sufficiently common (5%), other studies have reported that over 60% of LBP presentations to the ED are “benign” or “nonspecific” as they lack the concerning (so‐called “red flags”) symptoms used to identify high‐risk patients described in various guidelines . Clinical practice guidelines (CPG) and several international campaigns recommend that lumbar spine imaging be avoided in the ED for adults with nontraumatic LBP in the absence of these red flags.…”
mentioning
confidence: 99%